Changes in Nutrient Concentrations of Maize Zea mays var. intendata Leaves under Potassium and Magnesium Applications in Central Anatolia - Mehmet Zengin; Hakan Ertiftik (Journal of Agricultural Sciences)
This research was carried out to determine the effects of potassium 0, 40, 80, 120 kg K2O ha-1; as potassium sulfate; 50% K2O and magnesium 0, 20, 40, 60 kg MgO ha-1; as magnesium sulfate; 16% MgO applied to the soil, either separately or in various combinations, on some nutrients N, P, K, Ca, Mg, Fe, Zn in maize leaves grown under field conditions in semi-arid Central Anatolia in Turkey in 2009 and 2010. The study was designed as a factorial arrangement in randomized block design with four replications. After soil analysis of the study areas, K and Mg-fertilizers were applied at sowing. The results showed that the K applications alone could increase the nutrient concentrations of the leaves, and synergic relations were found between K and P, Fe, or Zn. Synergic relations were also found between Mg and P or Fe. Generally, combined applications of K and Mg resulted in higher nutrient concentrations in the leaves by ameliorating the antagonistic effect of poor soil K-Ca-Mg ionic balances. The leaf nutrient concentrations were generally higher in the first year 2009 than that of the experiment than in the second year 2010